My House, My Rules: A Comparative Case Study of How Organizational Culture and AI Interact to Shape Change in Organizational Routines at IKEA and Ericsson - Han,Bilge Su; Teuber,Sofia (2026)
AI integration is reshaping organizational work, however its success depends less on technical capability than on the cultural context into which it is introduced. This comparative case study examines how organizational culture and AI interact to shape organizational routines at two large Swedish organizations with distinct cultural profiles: IKEA, with its people-first, values-driven identity, and Ericsson, defined by an engineering-oriented precision culture. Drawing on 14 semi-structured interviews, it is observed that cultural orientation conditions how widely AI-driven routine change spreads, but that implementation factors such as leader participation, tool design, and the pacing of introduction, determine whether cultural readiness translates into actual transformation. Both organizations accepted AI for peripheral tasks while instinctively defending identity-constituting work from it, a pattern that held regardless of overall cultural openness. Organizational overwhelm is also identified as a distinct barrier to consolidation, and the playground phase is proposed as a transitional state in AI-driven routine change. Theoretically, the study refines the ostensive/performative framework by accounting for cultural mediation, sociomaterial tool design, and structural conditions of introduction.
Keywords: Organizational Routines; Organizational Culture; Artificial Intelligence; Sociomateriality; Ostensive/Performative Distinction